2012
DOI: 10.1007/s13193-012-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Oral Squamous Cell Cancer in a Tertiary Level Medical College Hospital: A 10 Yr Study

Abstract: To know the clinical and epidemiological characteristics & management strategies for the patients who underwent surgery for oral Squamous Cell Cancer (SCC) in a medical college hospital. Data pertaining to clinico-epidemiological factors & surgical management for oral cancer were analyzed in patients admitted to a tertiary level medical college hospital. Records of 139 patients admitted over a period of 10 years (January 1998 to December 2007) were used for data analysis. Only patients with complete records we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…[19] In the present study, the most common substance abuse was tobacco use (in any form other than smoking; 70%) followed by alcohol abuse (63.33%) and smoking (33.33%). The results of the study can be compared with those of the study conducted by Sharma et al [19] This study found that the most common substance abuse was tobacco chewing (47%) followed by smoking (40%) and alcohol (12%). Another similar study was conducted by Kumar V et al, which reported that the most common form of substance abuse in patients with SCC of the gingivobuccal complex was smokeless tobacco (68.75%) followed by smoking (39.58%) and alcohol (12.5%).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…[19] In the present study, the most common substance abuse was tobacco use (in any form other than smoking; 70%) followed by alcohol abuse (63.33%) and smoking (33.33%). The results of the study can be compared with those of the study conducted by Sharma et al [19] This study found that the most common substance abuse was tobacco chewing (47%) followed by smoking (40%) and alcohol (12%). Another similar study was conducted by Kumar V et al, which reported that the most common form of substance abuse in patients with SCC of the gingivobuccal complex was smokeless tobacco (68.75%) followed by smoking (39.58%) and alcohol (12.5%).…”
Section: Discussionmentioning
confidence: 48%
“…[18] The study found that in 53.33% cases SCC was well differentiated and moderately differentiated SCC was seen in 30% cases; and poorly differentiated SCC was found in 16.67% cases, which is comparable with the study conducted by Khandekar, [21] which reported 33.75% cases of well-differentiated, 27.5% cases of verrucous-differentiated, 20% cases of moderately differentiated and 18.75% cases of poorly differentiated oral cancers. [21] This study can be compared with that conducted by Sharma et al, [19] which reported that tumour size was T1 in 18%, T2 in 59%, T3 in 13% and T4 in 10% cases, whereas lymph node involvement was clinically absent in 33% of cases. In rest of the cases, clinical nodal staging was as follows: N1 16%; N2 51%; and N3 nil.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The site occurrence would include either soft tissues or jaw bones. Common malignancy with this sign includes Squamous cell carcinoma, 4 Basal cell carcinoma, 11 Salivary gland malignancies, 20 Sarcoma, 21 Melanoma, 22 Lymphoma, 23 Intra osseous malignancies of maxilla and mandible 24 and Metastatic malignancies.…”
mentioning
confidence: 99%